2020
DOI: 10.1186/s12882-020-02202-z
|View full text |Cite
|
Sign up to set email alerts
|

Combination of biomarker with clinical risk factors for prediction of severe acute kidney injury in critically ill patients

Abstract: Background Acute kidney injury (AKI) occurs commonly in the intensive care unit (ICU). Insulin-like growth factor-binding protein 7 (IGFBP7) and tissue inhibitor of metalloproteinase-2 (TIMP-2), known as [TIMP-2] x [IGFBP7] (NephroCheck), have been identified as novel biomarkers for the prediction of AKI risk. However, the effective use of disease biomarkers is indispensable from an appropriate clinical context. We conducted a retrospective cohort study to find risk factors and assess the perfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…SII integrates the predictive power of the three indicators (neutrophils, lymphocytes and platelet counts), which may potentially reflect the balance of the inflammatory, immune and thrombotic pathways. Furthermore, compared to other new biomarkers, including neutrophil gelatinase-associated lipocalin (NGAL), insulin-like growth factor-binding protein 7 (IGFBP7), tissue inhibitor of metalloprotease-2 (TIMP-2) and high mobility group box-1 (HMGB-1), SII is convenient and cost-effective [ 37 , 38 , 39 ]. Hu et al [ 15 ] found that SII contributed to the risk stratification of hepatocellular carcinoma (HCC) patients.…”
Section: Discussionmentioning
confidence: 99%
“…SII integrates the predictive power of the three indicators (neutrophils, lymphocytes and platelet counts), which may potentially reflect the balance of the inflammatory, immune and thrombotic pathways. Furthermore, compared to other new biomarkers, including neutrophil gelatinase-associated lipocalin (NGAL), insulin-like growth factor-binding protein 7 (IGFBP7), tissue inhibitor of metalloprotease-2 (TIMP-2) and high mobility group box-1 (HMGB-1), SII is convenient and cost-effective [ 37 , 38 , 39 ]. Hu et al [ 15 ] found that SII contributed to the risk stratification of hepatocellular carcinoma (HCC) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in another study of Nephrocheck®, its predictive performance was also low 21 . In a further study of 577 ICU patients, Nephrocheck®'s AUROC for AKI was also reported at 0.66 22 …”
Section: Discussionmentioning
confidence: 87%
“…Serum creatinine-based estimates are known to have limitations, especially in ICU patients [ 28 ]. Numerous novel diagnostic biomarkers have been identified over recent years [ 28 , 29 , 30 , 31 ]. These biomarkers have proven useful in predicting acute kidney injury and, in some cases, outperform serum creatinine.…”
Section: Discussionmentioning
confidence: 99%